A patient decision aid for antidepressant use in pregnancy: study protocol for a randomized controlled trial. Issue 1 (December 2016) - Vigod, Simone; Hussain-Shamsy, Neesha; Grigoriadis, Sophie; Howard, Louise; Metcalfe, Kelly; Oberlander, Tim; Schram, Carrie; Stewart, Donna; Taylor, Valerie; Dennis, Cindy-Lee
Abstract Background Many women with depression experience significant difficulty making a decision about whether or not to use antidepressant medication in pregnancy. Patient decision aids (PDAs) are tools that assist patients in making complex health decisions. PDAs can reduce decision-making difficulty and lead to better treatment outcomes. We describe the methods for a pilot randomized controlled trial of an interactive web-based PDA for women who are having difficulty deciding about antidepressant drug use in pregnancy. Methods/Design This is a pilot randomized controlled trial that aims to assess the feasibility of a larger, multi-center efficacy study. The PDA aims to help a woman: (1) understand why an antidepressant is being recommended, (2) be knowledgeable about potential benefits and risks of treatment and non-treatment with antidepressants, and (3) be clear about which benefits and risks are most important to her, with the goal of improving confidence in her decision-making. We include women aged 18 years or older who are: (1) planning a pregnancy or are pregnant (gestational age less than 30 weeks), (2) diagnosed with major depressive disorder, (3) deciding whether or not to use a selective serotonin reuptake inhibitor (SSRI) or serotonin norepinephrine reuptake inhibitor (SNRI) antidepressant in pregnancy, and (4) having at least moderate decision-making difficulty as per a Decisional Conflict Scale (DCS) Score ≥25. Participants are randomized to receive the PDA or an informational resource sheet via a secure website, and have access to the stated allocation until their final study follow-up. The primary outcomes of the pilot study are feasibility of recruitment and retention, acceptability of the intervention, and adherence to the trial protocol. The primary efficacy outcome is DCS score at 4 weeks post randomization, with secondary outcomes including depressive and anxiety symptoms. Discussion Our PDA represents a key opportunity to optimize the decision-making process for women around antidepressants in pregnancy, leading to effective decision-making and optimizing improved maternal and child outcomes related to depression in pregnancy. The electronic nature of the PDA will facilitate keeping it up-to-date, and allow for widespread dissemination after efficacy is demonstrated. Trial registration This trial is registered on ClinicalTrials.Gov under the identifierNCT02308592 (first registered: 2 December 2014).